2023
DOI: 10.3390/foods12030590
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Extraction from Residues of the Cocoa Fruit (Theobroma cacao L.) by Different Organic Acids: A Comparative Study

Abstract: Ecuador is the world’s fifth largest cocoa producer, generating hundreds of tons of residues from this fruit annually. This research generates value from the residual (cocoa pod husk) by using it as raw material to obtain pectin, which is widely used in the food and pharmaceutical industries. Extraction of three different organic acids with GRAS status (safe for use), the citric, malic and fumaric acids, was studied. In addition, two other factors, temperature (70–90 °C) and extraction time (60–90 min), were e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…This novel study demonstrated that other organic acids with GRAS status, besides the traditionally used citric acid, such as malic and fumaric acids, could extract pectin from this agricultural residue [14]. As in Case Study No.…”
Section: Case Study Nomentioning
confidence: 61%
See 2 more Smart Citations
“…This novel study demonstrated that other organic acids with GRAS status, besides the traditionally used citric acid, such as malic and fumaric acids, could extract pectin from this agricultural residue [14]. As in Case Study No.…”
Section: Case Study Nomentioning
confidence: 61%
“…All this had to be massively and quickly implemented since May 2019, when the number of infections and deaths with the SARS-CoV-2 virus in the country increased significantly, and it was decided to limit access to public and private sector institutions [14]. In a short time, hundreds of teachers took accelerated courses that gave them the knowledge they needed to switch from face-toface to virtual distance education [7].…”
Section: Institutional Strategies Adopted By the University During Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…En todo el proceso productivo se generan subproductos como, la mazorca que está constituido por (endocarpo, mesocarpo y exocarpo) (Ramírez et al, 2018), el mucilago, lixiviado y cascarilla (Handojo et al, 2019). Por lo general estos subproductos eran desechados; sin embargo, en la actualidad se le está dando amplia importancia debido a sus potencialidades nutritivas y disponibilidad (Jarrín-Chacón et al, 2023). Los subproductos de cacao son una alternativa potencial en la alimentación animal por su disponibilidad, precio bajo y su valor nutricional (Figueiredo et al, 2018), debido a que la industria pecuaria enfrenta a una diversidad de problemas, entre ellos el más representativo es la alimentación y nutrición animal, debido a que se requiere grandes cantidades de insumos alimenticios que cada dada vez son más caros (García et al, 2022).…”
Section: Introductionunclassified
“…31 In addition to its conventional uses in the food industry, pectin extracted from cocoa waste holds potential for various other applications as an emulsifier and recyclable surfactant in the formulation of environmentally friendly detergents. 32 It serves as a chelating agent in detergents, contributing to their enhanced performance and can be used in the development of edible packaging, offering a sustainable alternative to conventional packaging materials. 33 Ultrasonic waves with frequencies exceeding 20 kHz propagate through the material, creating alternating cycles of compression and shearing forces, which give rise to the formation of cavitation bubbles.…”
Section: Introductionmentioning
confidence: 99%